2003
DOI: 10.1161/01.atv.0000105055.68038.29
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Status and Polymorphisms of Methylenetetrahydrofolate Reductase Are Not Associated With Restenosis After Stenting in Coronary Arteries

Abstract: Objective-We investigated the influence of elevated homocysteine plasma levels and 2 polymorphisms, 677C/T and 1298A/C, of the methylenetetrahydrofolate reductase (MTHFR) gene on the risk of restenosis after stenting in patients with symptomatic coronary artery disease. Methods and Results-Homocysteine levels and MTHFR genotypes were determined in 800 consecutive patients treated with coronary artery stenting. Angiographic restenosis (Ն50% diameter stenosis at 6-month follow-up) was present in 25.8% of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
1
9
2
1
Order By: Relevance
“…The contribution of MTHFR polymorphisms and changes in plasma homocysteine levels to CAD pathogenesis were reported with inconsistent results [10,11,14,15]. Our results demonstrated select associations between MTHFR C677T, but not A1298C, alleles and genotypes, with CAD, highlighted by the increased prevalence of the 677T allele and 677T-containing genotypes (677C/T and 677T/T) among CAD patients compared to controls.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The contribution of MTHFR polymorphisms and changes in plasma homocysteine levels to CAD pathogenesis were reported with inconsistent results [10,11,14,15]. Our results demonstrated select associations between MTHFR C677T, but not A1298C, alleles and genotypes, with CAD, highlighted by the increased prevalence of the 677T allele and 677T-containing genotypes (677C/T and 677T/T) among CAD patients compared to controls.…”
Section: Discussioncontrasting
confidence: 53%
“…MTHFR 677T/T is associated with significantly elevated homocysteine levels, and thus precipitates enhanced CAD risk [10][11][12], particularly in the presence of low folate [13]. Others suggested no association [14,15], or association only with folate deficiency whereby low-normal serum folate may prevent the onset or attenuate CAD development [13]. In contrast to the C677T polymorphism, the A1298C polymorphism is not associated with CAD [11,16]; although one report claimed that A1298C heterozygosity, acting by elevating homocysteine, was associated with CAD [17].…”
Section: Introductionmentioning
confidence: 99%
“…There was also no relation of this genetic alteration with the risks of in-stent restenosis [Koch et al, 2003a] and graft atherosclerosis in patients with CABGs [Iwama et al, 2001], respectively. In contrast to these negative findings, a couple of small studies Botto et al, 2004] reported that the sequence variation influenced the size of the vessel area affected by intimal hyperplasia ] and the outcome after PTCA or CABG surgery [Botto et al, 2004], respectively.…”
Section: Oxidative-antioxidative Systemmentioning
confidence: 89%
“…Concluíram que a distribuição dessas duas variantes da MTHFR era semelhante e que nenhuma delas se correlacionava com coronariopatia na população árabe 40 . Nesse mesmo ano, Koch et al 41 investigaram a influência da HHcy e dos dois polimorfismos da MTHFR no risco de re-estenose em seis meses após angioplastia com "stent" em 800 pacientes coronariopatas sintomáticos. A taxa de re-estenose foi semelhante entre aqueles com HHcy e aqueles com homocisteinemia normal.…”
Section: P R I N C I P a I S D E T E R M I N A N T E S D E Hiperhomocunclassified